A New Perspective on Media Ethics - Abdul Azim Noorbakhsh (Genius Journals, 2022)
Regarding the media’s deep impact on current human live, it can be resembled as an intelligent social-cultural institute. And, considering on its targeted and active communications with its self-management capabilities on its processes, we can call the media as a living organism similar to the human. Therefore, with understanding the ethnical characteristic of a communicative human and implementing theme on the media, we can explore the media’s ethical responsibilities, and we can explore the relationships between ethic and media from the Anthropology aspect. In this article, we will investigate the Media with the recognitions of two concepts morality and Ethics. Also, I will search in the category of dimensions and fields of ethics in the media. Based on this, the fundamental principles influencing media ethics and effective non-media factors in its construction and role are researched and relying on the normative theory of social responsibility, the category of media ethics goes beyond the concept of individual ethics and journalistic ethics, separate from the broad and pervasive ethical dimension. It should be considered and comprehensive research should be done in the field
Keywords: New Perspective; Media Ethics; Institutional; Professional